The Influence of Career Development, Communication and Discipline on Employee Job Satisfaction at PT. Anra - Melkyory Andronicus; Van Three Vernando (Kusuma Negara Business School, 2020)
The researcher chose PT Anra as the location of the research. The research objects are employees who work at PT Anra. High job satisfaction will be a driving factor in supporting employees so that it can be a motivation to perform their best. Performance has decreased, presumably due to career development, communication, discipline and job satisfaction of employees in the company. Career development is a transfer of positions given to employees in the form of demotion or transfer of positions given. Career development is needed to make employees have a new work flow and work experience in a particular job field. The process of exchanging information in carrying out work can be referred to as. Discipline is a form of willingness that employees have in following the work regulations set by the company. With high discipline, the company will be able to form a good work culture among employees. This study uses a saturated sampling technique. The population use determination was 114 people and for testing the validity data was taken from the branch office. Theories used to support research are human resource management theories related to career development, communication, discipline and job satisfaction. The approach taken by researchers uses quantitative in all methods used. The data collected through the process of interviews, questionnaires and documentation study. The analysis used includes methods of multiple linear regression, coefficient of determination and simultaneous test (F-test) (23,524> 3,12) on the value of the partial test (t-test) (2,717> 1,976), (3,473> 1,976) and ( 6,761> 1,976). The conclusion of the final results in this study, the variables career development, communication and discipline simultaneously and partially have a significant positive effect on job satisfaction with the coefficient of determination with a ratio of 37.4%.